2010
DOI: 10.2320/matertrans.mc200913
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Properties of TiAlN/a-C Nanocomposite Coatings Prepared by Reactive Sputtering

Abstract: TiAlN/a-C nano-composite coatings were synthesized by a reactive co-sputtering process to investigate the effects of sputtering conditions on the microstructure and mechanical properties. Coating films were deposited on square plates of Si and high speed steel (ANSI M2) by the cosputtering of TiAl (pulsed-d.c. sputtering) and C (d.c. sputtering) targets using a ''Facing Target-type Sputtering'' system at an atmosphere with a mixture of Ar and N 2 but without hydrocarbon gas. The structure of the coatings was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…The column boundary area is also completely amorphous. Thus, according to the definition described in literature [9][10][11][12][13][14][15][19][20][21][22], the TiAlVCN coatings can be termed as nanocomposites of nc-TiAlV(N,C)/a-C, namely nano-crystalline TiAlV(N,C) and amorphous carbon.…”
Section: High Resolution Tem Of Nanmentioning
confidence: 99%
See 2 more Smart Citations
“…The column boundary area is also completely amorphous. Thus, according to the definition described in literature [9][10][11][12][13][14][15][19][20][21][22], the TiAlVCN coatings can be termed as nanocomposites of nc-TiAlV(N,C)/a-C, namely nano-crystalline TiAlV(N,C) and amorphous carbon.…”
Section: High Resolution Tem Of Nanmentioning
confidence: 99%
“…Carbon is known to have multiple sp, sp 2 and sp 3 binding characteristic, and thereafter may have a series of different condensed structures having diverse physical and mechanical properties. Considering the fact that carbon coatings, mostly diamond like carbon (DLC), have environment-dependent low friction coefficient, more recently the research interests have been focused in the growth of carbon-containing TMN coatings, such as Ti-N-C [18][19][20][21], Ti-Al-N-C [22][23][24], Zr-N-C [25] and Ti-Si-C-N [26][27], which show both high hardness and environment-dependent low friction. It has been found that a transition from columnar nitride crystallites to a dual-phase structure occurs as a result of the precipitation of free carbon in the coating structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated that multilayer coatings can exhibit high hardness and fracture resistance with low compressive stress through control of the parameters of the layered structure [5,17]. The tribological behavior of carbon-based thin films is also strongly influenced by their chemical composition, polycrystalline structure, and surface morphology [18].…”
Section: Introductionmentioning
confidence: 99%
“…Films of diamond-like carbon (DLC) and transition-metal and carbon nitrides (CNx), such as titanium aluminum nitride (TiAlN) and CNx are the most widely used coatings for tribological applications, such as for forming and cutting tools. Thus, it is desirable to improve the tribological properties of these films to enhance their performance in tool applications [5].…”
Section: Introductionmentioning
confidence: 99%